Stoichiometric partially-protonated states in hydroxide perovskites: the jeanbandyite enigma revisited. (1st April 2017) - Welch, Mark; Kampf, Anthony
The original description of the hydroxide perovskite jeanbandyite gives a formula (Fe3+1–x, x)(Sn1–y, y) (OH)6 ( = vacancy), which implies the possibility of stoichiometric vacancies at B and B' sites. The validity of this formula has been questioned subsequently. Furthermore, jeanbandyite has metrically a cubic unit cell, but it is optically uniaxial. It is clear that a structure determination is needed to clarify the nature of this enigmatic mineral. Previous studies could find no crystals of sufficient quality for structure determination using X-ray diffractometers available at the time. Crystals of jeanbandyite from Hingston Down, Cornwall, UK and the type locality Llallagua, Bolivia, have been found that are of a quality that allows structure refinement by single-crystal X-ray diffraction. Structural data for crystals from each locality are presented that clarify the nature of jeanbandyite and raise some interesting questions concerning the significance of partially deprotonated states in perovskite-type structures. The structures of both jeanbandyite crystals are cubic with space group Pn3 and unit-cell parameters a = 7.658(2) Å (Llallagua) and 7.6427(2) Å (Hingston). The octahedral tilt system is a+a+a+ and corresponds to that of the aristotype of BB'(OH)6 hydroxide double perovskites. Structure determination demonstrates that B is very Fe3+-rich and B' is filled by Sn, thereby requiring revision of the general jeanbandyite formula to Fe3+xFe2+(1–x)Sn(OH)(6–x)Ox for 1≥ × > 0.5, with an ideal end-member formula Fe3+Sn(OH)5O. As such, jeanbandyite corresponds to oxidized natanite with partially deprotonated oxygen sites. This stoichiometry cannot be represented in space group Pn3 for the observed unit cell as it implies more than one non-equivalent oxygen atom. Consequently, it is inferred that there is no long-range ordering of deprotonated oxygen sites. It is, however, conceivable that the uniaxial optical character of jeanbandyite is linked to the local short-range order of deprotonated domains.